(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يمكن القول إن السياحة هي صناعة المستقبل ، ولا يزال تقدمها وتوسعها وتطورها ينمو بصورة سريعة جداً ، حيث تشير توقعات منظمة السياحة العالمية أن عدد السياح لعام 2020 سيصل إلى مليار وستمائة مليون سائح, وتمتلك سورية الكثير من مقومات الجذب السياحية المميزة وبما يؤهلها لتكون قبلة للسياحة العالمية ومقصداً للاستثمار السياحي المجدي اقتصادياً. ولا تزال صناعة السياحة في سوريا ناشئة لذا يهدف البحث إلى دراسة وتحليل وبيان الأهمية الاقتصادية للسياحة وتأثيراتها المختلفة ودراسة العلاقة الارتباطية بين مختلف المتغيرات وقياس فاعلية سياسات التسويق والترويج السياحي التي تتبعها الإدارة السياحية لتحسين واقع الصناعة السياحية وقد توصل البحث لعدة نتائج أهمها تطور الصناعة السياحية في سورية خلال الفترة المدروسة كما نجحت الإدارة السياحية في تنشيط وجذب الاستثمارات وخلص البحث إلى بعض التوصيات لتفعيل النشاط السياحي والارتقاء بالصناعة السياحية إلى المستوى المأمول. It can be said that tourism is the future industry. Tourism advances, extends, and develops rapidly. Expectations of International Tourism Organization state that the tourists’ numbers for 2020 will be one billion and six hundred million tourists, Syria has several and exceptional tourist attractions. It is security and safety which allow Syria to be the world’s destination for the profitable tourist investments. The tourism industry is still primitive, and the study analyzes the facts during the period stated. It shows the importance of tourism and its economic impact. Moreover, it studies the relation among the variables and the efficiency of tourist promotion and marketing in order to improve this industry to make Syria one of the leading countries in tourism industry. The main results are: Tourism industry has developed during the period studied, and the tourism administration had succeeded in attracting investments. The research states a set of recommendations to improve tourist activities and to let this industry grow to desired level.